The design development and evaluation of an active control aircraft model wind tunnel facility. - Malik, I.A. (Cranfield University, 1982)
Recent progress in the field of Active Controls Technology(ACT) has resulted in increased interest in dynamic wind tunnel testing for basic research. The present work reports the findings of a three year research and development programme to build a dynamic wind tunnel testing facility. The task included the design and construction of a controllable dynamically scaled aircraft model, a suspension system to give the model four degrees of freedom, and an electronic control unit to interface with the model for operating the primary controls, for stability augmentation and for providing output signals for measurement purposes. The dynamic characteristics of the model have been recorded for some simulated representative flight conditions and are compared with theoretical predictions and the expected characteristics derived from full size aircraft data. The use of various stability augmentation functions has also been investigated to assess the usefulness of the electronic control unit as a means for providing stability augmentation. The results show the system to have considerable potential as an ACT Simulator. Modifications are suggested for further development of the facility to achieve a higher degree of accuracy and versatility.